Clearance of 99mTc DTPA from guinea pig nasal, tracheobronchial, and bronchoalveolar airways. Issue 11 (November 1990) - Greiff, L; Wollmer, P; Erjefält, I; Pipkorn, U; Persson, C G
Abstract : Technetium-99m labelled diethylenetriamine penta-acetate (99mTc-DTPA) was used to compare small solute absorption (clearance) from nasal, tracheobronchial, and bronchoalveolar airways in anaesthetised guinea pigs. 99mTc DTPA dissolved in saline was superfused through nasal and orolaryngeal catheters on to nasal and tracheobronchial airways; a small particle aerosol of nebulised 99mTc DTPA was delivered to the bronchoalveolar airways through a tracheostomy. Radioactivity over the appropriate region was then determined with a gamma camera. Mucociliary transport of 99mTc DTPA appeared not to contribute to the disappearance of 99mTc DTPA. Time-activity curves were obtained and half life values calculated by fitting a monoexponential equation to the experimental data. A progressive reduction in 99mTc DTPA was recorded from the nasal and tracheobronchial airways and from the bronchoalveolar airway, suggesting that absorption was occurring. The disappearance of 99mTc DTPA was fastest from the bronchoalveolar region, which also had the largest mucosal surface. The similar shape of the retention curves for the nasal and tracheobronchial regions suggests that the characteristics of nasal absorption of 99mTc DTPA could prove applicable to the tracheobronchial region. It is proposed that the present methods are suited for comparing the pharmacology of small solute absorption across nasal, tracheobronchial, and bronchoalveolar airway mucosa.